2002
DOI: 10.1053/rapm.2002.30671
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine added to the local anesthetic for axillary brachial plexus block prolongs postoperative analgesia

Abstract: Buprenorphine-local anesthetic axillary perivascular brachial plexus block provided postoperative analgesia lasting 3 times longer than local anesthetic block alone and twice as long as buprenorphine given by IM injection plus local anesthetic-only block. This supports the concept of peripherally mediated opioid analgesia by buprenorphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 13 publications
2
63
0
4
Order By: Relevance
“…In another study, Candido et al took a critical look at the properties of buprenorphine as an adjuvant added to local anaesthetics. They compared the effect of administration of buprenorphine in the area of the brachial plexus (group I) and intramuscularly (group II) to the effect of not using buprenorphine (group III) [19]. Visual analogue (VAS) scores for pain were lowest in group I (2.5 pts.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Candido et al took a critical look at the properties of buprenorphine as an adjuvant added to local anaesthetics. They compared the effect of administration of buprenorphine in the area of the brachial plexus (group I) and intramuscularly (group II) to the effect of not using buprenorphine (group III) [19]. Visual analogue (VAS) scores for pain were lowest in group I (2.5 pts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human patients have shown that by mixing an opioid with the local anesthetic, patients who undergo surgery experience an extended duration of postoperative analgesia. 10,11 Proving similar synergistic effects in veterinary patients would be challenging, and there has not been proof that the addition of opioids administered locally benefits veterinary patients who undergo oral surgery. Anecdotally, the authors of this chapter regularly use microdoses of buprenorphine (15 μg) mixed within the local anesthetic and distributed into as many regional block locations as clinically indicated and believe these patients benefit from the local opioid use.…”
Section: Drug Selectionmentioning
confidence: 99%
“…10 Needle placement for the major palatine nerve block -the needle should be placed and advanced through the palatal mucosa, with needle tip terminating at the rostral extent of the landmarks of the area where the major palatine may exist.…”
mentioning
confidence: 99%
“…[30][31][32] Buprenorphine, 0.3 mg, also prolongs anesthesia and analgesia, but at the expense of nausea and vomiting. 33 Dexamethasone can also prolong intermediate-acting agents to a degree similar to epinephrine, but the optimal dose and any potential long-term effects of dexamethasone remain uncertain. 34,35 The beneficial effects of these additives, as well as their potential neurotoxicity, alone and in combination, are currently still under investigation.…”
Section: Pharmacologic Considerationsmentioning
confidence: 99%